EFISIENSI PEMANFAATAN PUPUK ANORGANIK MELALUI APLIKASI BOKASHI GAMAL PADA TANAMAN CABAI MERAH BESAR HIBRIDA (Capsicum annuum L.) - Alimuddin, Suraedah; Edy, Edy; Haris, Abdul (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2024)
The purpose of this study was to determine the efficiency of inorganic fertilizer utilization through the use of bokashi from Gliricidia sepium on large hybrid chili plants and its effects on the physical and chemical properties of the soil as well as plant growth and productivity. This study was conducted in Pakkabba Village, North Galesong District, Takalar Regency, and soil, bokashi, and leaf tissue analysis was carried out at the Soil Laboratory of the Agricultural Assessment and Technology Center (BPTP) Maros. This research was conducted using a Randomized Block Design with 8 treatments: 100% inorganic fertilizer (ZA 650, Urea 250, SP36 500, and KCl 450 kg.ha-1); 90% inorganic fertilizer + Bokashi of Gliricidia sepium 5 t.ha-1; 80% inorganic fertilizer + Bokashi of Gliricidia sepium 10 t.ha-1;  70% inorganic fertilizer + Bokashi of Gliricidia sepium 15 t.ha-1; 60% inorganic fertilizer + Bokashi of Gliricidia sepium 20 t.ha-1; 50% inorganic fertilizer + Bokashi of Gliricidia sepium 25 t.ha-1; Without inorganic fertilizer + Bokashi Gliricidia sepium 30 t.ha-1. The results showed that the application of Gliricidia sepium bokashi did not have a significant effect on the level of soil porosity. The application of Gliricidia sepium bokashi increased the residue of N, P, K soil, C-organic, CEC, and soil pH at the end of the study. Inorganic fertilizer 70% of the recommended dose + 15 t.ha-1 Gliricidia sepium bokashi provided significantly better hybrid large chili productivity compared to other treatments, namely 22.11 t.ha-1. Gliricidia sepium bokashi 30 t.ha-1 without inorganic fertilizer produced chili productivity that was no different from the treatment of 100% inorganic fertilizer. These results indicate that the use of 30 t.ha-1 Gliricidia sepium bokashi can save 100% of inorganic fertilizer (650 kg ZA, 250 kg urea, 500 kg SP-36, and 450 kg KCl) in large chili plantings so that the use of 30 t.ha-1 Gliricidia sepium bokashi without inorganic fertilizer can be an alternative for organic cultivation of hybrid large chili plants.